Realization of ppm-level CO detection with exceptionally high sensitivity using reduced graphene oxide-loaded SnO2 nanofibers with simultaneous Au functionalization. Issue 19 (12th February 2016) - Kim, Jae-Hun; Katoch, Akash; Kim, Hyoun Woo; Kim, Sang Sub
Abstract : We have realized the highly sensitive, selective ppm-level carbon monoxide (CO) detection based on graphene oxide (RGO) nanosheets-loaded SnO2 nanofibers with simultaneous Au functionalization. Abstract : We have realized the highly sensitive, selective ppm-level carbon monoxide (CO) detection based on graphene oxide (RGO) nanosheets-loaded SnO2 nanofibers with simultaneous Au functionalization. The interplay between RGO/Au and SnO2 in terms of transfer of charge carriers and modulation of potential barriers is responsible for the exceptionally high CO detectability.